Resonance scattering and absorption of light by finite two-period gratings of circular silver nanowires - Natarov, D.M.; Sauleau, R.; Nosich, A.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
We consider the two-dimensional scattering of the H-polarized
electromagnetic plane waves of the visible range by three types of gratings made of
periodically arranged circular cylindrical sub-wavelength wires. Using the field
expansions in local coordinates and addition theorems for cylindrical functions, we
obtain a block-type matrix equation for the field expansion coefficients. This equation is
of the Fredholm second-kind form that guarantees convergence of numerical solution.
The scattering and absorption cross-sections and the near-field patterns are computed.
The interplay of plasmon and grating-type resonances is studied for two and three-layer
gratings of identical periods, stacked two-period gratings, and in-line two-period gratings
made of nano-diameter silver wires.